Recommendations for the probity of computer evidence. (2021) - Marshall, Paul; Christie, James; Ladkin, Peter Bernard; Littlewood, Bev; Mason, Stephen; Newby, Martin; Rogers, Jonathan; Thimbleby, Harold; Thomas, Martyn
No abstract available